7c+3-5c=12

Simple and best practice solution for 7c+3-5c=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7c+3-5c=12 equation:


Simplifying
7c + 3 + -5c = 12

Reorder the terms:
3 + 7c + -5c = 12

Combine like terms: 7c + -5c = 2c
3 + 2c = 12

Solving
3 + 2c = 12

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 2c = 12 + -3

Combine like terms: 3 + -3 = 0
0 + 2c = 12 + -3
2c = 12 + -3

Combine like terms: 12 + -3 = 9
2c = 9

Divide each side by '2'.
c = 4.5

Simplifying
c = 4.5

See similar equations:

| 2r+20= | | 19x+178=11x+106 | | 4=3w-2 | | 4=pirt | | 5(k-8)=-1(7+k) | | 6=d+18 | | 7t-6=1569 | | 2(-4-7k)+4(1+7k)=-60 | | 8x+7x=54 | | 6x+12=4x+22 | | 4x+23=x+5 | | 3x-24+12=15-6x | | 8x-15=5x-3 | | (2x-5)=2(3x-2) | | 7x+23=3x+3 | | (3x-5)=5x-2 | | 5(a-4)=5a-4 | | 0.77+0.15t=1.47t-0.11 | | 3x+1.5=15.5 | | 7x-3=13x+33 | | -3-x=-10 | | 9x+8y=6 | | t-2=-1 | | 4x-7+3x=90 | | -4z-z= | | -2-6x=-38 | | 2x+21=9x-63 | | 6x+55=2x+27 | | 3(4x+5)=17x+12-5x+3 | | 6x+35+9x=15(x+2)-25 | | y+34=19 | | 3-9x=84 |

Equations solver categories